IL-6 Deficiency Attenuates Skeletal Muscle Atrophy by Inhibiting Mitochondrial ROS Production through the Upregulation of PGC-1α in Septic Mice. (27th April 2022) - Yang, Bo; Yang, Xiaoming; Sun, Xiangran; Shi, Jiaofang; Shen, Yi; Chen, Ren
Abstract : Current evidences indicate that both inflammation and oxidative stress contribute to the pathogenesis of sepsis-associated skeletal muscle atrophy. However, the interaction between inflammation and oxidative stress has not been completely understood in sepsis-associated skeletal muscle atrophy. Here in the present study, a murine model of sepsis has been established by cecal ligation and puncture (CLP) with wild-type and interleukin- (IL-) 6 knockout (KO) mice. Our results suggested that IL-6 KO largely attenuated skeletal muscle atrophy as reflected by reduced protein degradation, increased cross-sectional area (CSA) of myofibers, and improved muscle contractile function (all P < 0.05 ). In addition, we observed that IL-6 KO promoted the expression of peroxisome proliferator-activated receptor γ coactivator–1alpha (PGC–1 α ) and inhibited CLP-induced mitochondrial reactive oxygen species (ROS) production in skeletal muscles (all P < 0.05 ). However, the knockdown of PGC–1 α abolished the protective effects of IL-6 KO in CLP-induced skeletal muscle atrophy and reversed the changes in mitochondrial ROS production (all P < 0.05 ). Ex vivo experiments found that exogenous IL-6 inhibited PGC–1 α expression, promoted mitochondrial ROS production, and induced proteolysis in C2C12 cells (all P < 0.05 ). Together, these results suggested that IL-6 deficiency attenuated skeletal muscle atrophy by inhibiting mitochondrial ROS production through the upregulation of PGC–1 α expression in septic mice.